Navigating Differences in Institutions Toward Value Co-Creation - Smith, R-A; Rosenstreich, D; Holdershaw, J (University of Adelaide, 2018)
Much research has been conducted in the areas of value co-creation and the service encounter. However, there is a dearth of information on how these two areas are experienced by consumers and service providers who have different behavioural, social and cognitive approaches to the service encounter. This study will explore these approaches, called institutions, through the lens of the service dominant logic paradigm. The social services encounter is under-researched in the area of marketing and often presents an environment where the service providers and consumers differ in their institutions because of their varying social realities. Theoretically, the research will contribute to the services marketing literature on value co-creation and service encounters by providing insight into how service providers and consumers negotiate differences to co-create value. The research will also add to the literature by developing a construct to guide the testing of institutional variables within the services marketing discipline.
Keywords: value co-creation, institutions, service dominant logic